Lean manufacturing at Volvo Truck Production Australia : development of an implementation strategy - Berg, Andreas; Ohlsson, Fredrik (2005)
The world’s globalization and consolidation of multinational companies result in increased competition for manufacturing plants. A truck manufacturer in Australia, like Volvo, feels the demand from global shareholders as well as the local customers. A factory must always attempt to achieve world class manufacturing to survive in the long run. Therefore it is important for a local factory like Volvo’s Wacol plant to continuously develop their way of working. In order to become more productive and efficient, Volvo has decided to implement the Japanese production philosophy Lean Production. With consideration to this, Volvo wanted a comprehensive investigation of the current situation in the production. Volvo’s desire was that this Master’s Thesis report should end up in an implementation strategy that Volvo could use during the implementation. The project was to be based on a theoretical framework together with empirical studies in the factory. In consultation with Volvo and tutors from Chalmers University of Technology and Luleå University of Technology the report’s purpose was formed: The purpose of the Master’s Thesis is to develop a strategy for the implementation of lean production in the Wacol factory’s manufacturing area. In order to fulfil the purpose a thorough literature study within lean production was accomplished. This resulted in a theoretical framework that together with an empirical study of Volvo’s organization was the foundation of the report. In the empirical study a comprehensive questionary survey was accomplished among both white collars and blue collars. The survey was based on lean theories and the situation in the factory. The analysis of the situation in the factory showed that the organization has to change their way of working in some areas, in order to be prepared for the implementation of lean. First of all the managers have to work with the gap between white collars and blue collars. This gap has its root in the Australian union culture and it will be a major obstacle if it is not ...